CFD modelling of a pallet of heat-generating product applied to a cheese product. (August 2021) - Pham, Anh Thu; Moureh, Jean; Belaidi, Mourad; Flick, Denis
Abstract: This work aimed to numerically study the heat transfer and airflow within a pallet of heat-generating product. A computational fluid dynamics (CFD) model of palletized cheese inside a cold room was developed. The model took into account the effect of natural convection induced by the heat-generating product. A full-scale experimental set-up under controlled operating conditions was built to validate the model. The air velocity within the pallet was measured using Laser Doppler Velocimetry (LDV). Three heat fluxes and two upwind air velocities were chosen: Q = 0.05 W, 0.15 W and 0.30 W per product with a mass of 250 g; uair.in = 0.31 m.s −1 and 0.73 m.s −1 . The model predicted well both the product temperatures and airflow patterns. This model is a potential design tool to be used to optimize the cooling system of a heat-generating product. The model can also be adapted for other food products as well as other types of packaging.